2021
DOI: 10.17770/sie2021vol6.6399
|View full text |Cite
|
Sign up to set email alerts
|

Financial Sustainability of Higher Education Institutions

Abstract: Since the beginning of the XXI century, there have been clear modifications in the sector of higher education, when the institutions have moved near to the economic sector. These changes were primary introduced as the consecutive response to the transformation processes within the society, which should be embedded in the following construct: there was a clear move towards a more competitive and market-based system. Due to the changes in the operating environment financial sustainability and its management for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The findings revealed that several private universities are in financial jeopardy and are unable to assure students of a top-notch education in the coming years. In 2021, Kuzmina [62] did another analysis of the financial viability of the private higher education business in Latvia. The following findings have been reached by the author: Today's higher education administration is becoming more complex, necessitating the use of extra instruments to ensure long-term financial stability.…”
Section: Financial Sustainability Applications In Higher Educationmentioning
confidence: 99%
“…The findings revealed that several private universities are in financial jeopardy and are unable to assure students of a top-notch education in the coming years. In 2021, Kuzmina [62] did another analysis of the financial viability of the private higher education business in Latvia. The following findings have been reached by the author: Today's higher education administration is becoming more complex, necessitating the use of extra instruments to ensure long-term financial stability.…”
Section: Financial Sustainability Applications In Higher Educationmentioning
confidence: 99%
“…Others have proposed and tested various indicators and benchmarks to measure and compare the financial health of different institutions [21]. Some have focused on the specific challenges and opportunities faced by universities in certain regions or countries, such as the UK [22], OECD members [23], Latvia [24], and Zimbabwe [25]. Some have explored how universities can balance their autonomy, accountability, and innovation in financial reporting and management [26].…”
Section: Financial Sustainability In Higher Education Institutions (H...mentioning
confidence: 99%
“…Consequently, several research studies have concentrated on different schemes to attain financial sustainability in HEIs [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Some of these studies focused on factors affecting financial sustainability in HEIs [6,8,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Another study [12] also thoroughly reviewed the literature on sustainability funding in higher education. Other studies focused on region-specific financial sustainability challenges and opportunities in HEIs in countries and regions such as Zimbabwe [6], the United Kingdom [13], OECD country members [14], Kenya [17], Latvia [18], Malaysia [19], the Puntland State of Somalia [20], Indonesia [21], and China [25].…”
Section: Introductionmentioning
confidence: 99%